2018
DOI: 10.2174/1574884712666170509162523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crocin on Antibody Titers to Heat-Shock Protein 27 in Subjects with Metabolic Syndrome

Abstract: There was no significant effect of crocin on serum anti-Hsp27 titers in subjects with MetS, but this needs further confirmation in larger-scale trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Saffron also could not modulate diazinon‐induced disturbances in serum levels of ALT and AST in rats (Hariri et al, 2018). However, some studies have demonstrated that crocin modulated liver damages induced by different toxins in animal models (Algandaby, 2018; Velioglu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saffron also could not modulate diazinon‐induced disturbances in serum levels of ALT and AST in rats (Hariri et al, 2018). However, some studies have demonstrated that crocin modulated liver damages induced by different toxins in animal models (Algandaby, 2018; Velioglu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, a recent study in patients with allergic asthma showed a significant reduction in CRP concentrations following intake of 100 mg/day saffron (Hosseini, Zilaee, & Shoushtari, 2018). However, administration of crocin, as a main constituent of saffron, caused no significant influence on serum levels of CRP in patients with metabolic syndrome (Nosrati et al, 2018). It seems that synergetic effects of different constituents of saffron might explain most beneficial effects of this herbal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that saffron aqueous extract and, to some extent, crocin could effectively prevent reaching the criteria of MetS in schizophrenic patients who were treated with olanzapine . Furthermore, saffron and its active constituents have also shown anti-inflammatory effects in subjects with MetS. , In a study conducted by Kermani et al, forty-four adults diagnosed with MetS were randomly divided into 2 groups, to receive 100 mg/day saffron for 12 weeks. The authors reported that saffron is able to modulate the serum concentrations of several pro-inflammatory and anti-inflammatory cytokines such as vascular endothelial growth factor (VEGF), interleukin-6 (IL-6), and epidermal growth factor (EGF) .…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence studies have demonstrated that herbal remedies administration had no significant effect on oxidative stress and inflammation patients with T2DM (Azimi et al, ). Moreover, Nosrati et al () observed that crocin intake at a dosage of 15 mg twice a day for 8 weeks did not affect any significant effect on hs‐CRP and anti‐HSP27 titers in subjects with metabolic syndrome. The evidence demonstrated that saffron might be considered as a preventive or therapeutic agent against oxidative damage and inflammatory markers through several mechanisms, including modulating pro‐oxidant–antioxidant balance (Kermani et al, ), scavenging ROS, the inhibition of nuclear factor kappa B activation and TNF‐α production, decreased lipid peroxidation, enhanced antioxidant capacity, and the activation of PI3K/Akt signaling pathway (Razavi & Hosseinzadeh, ; Thushara et al, ; Yang et al, ; Yarijani et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, saffron administration for 12 weeks improved glycemic status and serum lipids in patients with Type 2 diabetes mellitus (T2DM; Moravej Aleali et al, ). Although other researchers failed to find an improvement in insulin and lipid profiles, depression, and metabolic parameters in response to ingesting saffron and crocin supplements (Nosrati et al, ; Pourmasoumi, Hadi, Najafgholizadeh, Kafeshani, & Sahebkar, ; Sahraian, Jelodar, Javid, Mowla, & Ahmadzadeh, ).…”
Section: Introductionmentioning
confidence: 99%